Sebaceous carcinoma of lacrimal gland with endophthalmitis - Aulia, Dinar; Irawan, Empi (International Journal of Research in Medical Sciences, 2022)
Sebaceous carcinoma (SC) is a rare type of cancer that aggressive which develops from the sebaceous glands and can impair patients’ visual acuity. It usually arises from the periorbital area, which commonly affects in the eyelid. This study discusses the sebaceous carcinoma of lacrimal gland with endophthalmitis. The patient was a 53-year-old Javanese man came with a chief complaint of no vision in his left eye, painlessness nowadays, no previous medical history, and slowly progressive swelling mass on the outer aspect of the left upper eyelid for a year duration. On examination, there was no light perception for the left eye and 6/7, 5 on the right eye. The tumor was rock hard and fixed on palpation, which caused partial upper eyelid ptosis, displaced the globe anteromedially, and impaired ocular motility. There was also a massive chemosis in the left eye, ptosis with corneal damage caused by endophthalmitis. The histopathological examination found that the tumor was composed of nests of cuboidal and columnar cells with proliferation round core cells, pleomorphic, hyperchromatic, vacuole cytoplasm, and prominent nuclei, arranged in a solid structure without lymphovascular invaded. The final diagnosis was sebaceous carcinoma of the lacrimal gland. The patient took tumor excision surgery followed by orbital evisceration due to endophthalmitis with post-operative radiotherapy as an alternative treatment. Sebaceous carcinoma of the lacrimal gland is extremely rare. There are no specific treatments, and it is difficult to study further for the best treatment due to its rare incidence. Sebaceous carcinoma of the lacrimal gland has so far been treated best by surgical excision and radiotherapy after.